The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.5935/0004-2749.2022-0035
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the visual axis through two different methods: quantification and differences for measuring chord μ

Abstract: To compare the differences between the apparent and actual chord μ. Methods: In this prospective, comparative, non-randomized, and non-interventional study, imaging examinations using Pentacam and the HD Analyzer were performed in the same room under the same scotopic conditions. The inclusion criteria were patients aged 21-71 years, able to provide informed consent, myopia up to 4D, and anterior topographic astigmatism up to 1D. Patients using contact lenses, those with previous eye diseases or surgeries, cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Given that pupil size decreases with age [ 29 ], differences in its value between previous studies [ 25 , 28 ] and our study may rise from the different age of cohorts. Previous studies included younger participants (30.69 ± 7.85 years [ 25 ] and 40.3 ± 16.9 years [ 28 ]) than in our study (mean, 67.2 ± 11.2 years). In addition, the devices use different principles.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Given that pupil size decreases with age [ 29 ], differences in its value between previous studies [ 25 , 28 ] and our study may rise from the different age of cohorts. Previous studies included younger participants (30.69 ± 7.85 years [ 25 ] and 40.3 ± 16.9 years [ 28 ]) than in our study (mean, 67.2 ± 11.2 years). In addition, the devices use different principles.…”
Section: Discussionmentioning
confidence: 76%
“…There was a statistically significant difference (1.8 ± 1.2 mm, p < 0.01) between the measurements of the two devices for healthy eyes. Rodrigues et al [ 25 ] reported that Pentacam showed a shorter pupil diameter (3.31 mm; range, 1.87 to 5.23 mm), than the HD analyzer (5.76 mm; range, 2.50 to 8.60 mm).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the lens' anterior surface is configured with a negative spherical aberration to counterbalance the cornea's positive spherical aberration. 15,16,[20][21][22][23][24][25][26][27][28][29][30] The advantages associated with the utilization of the TECNIS Synergy IOL in both eyes (hereinafter referred to as the ZFR00V IOL) and the potential enhancement of patient outcomes associated with the combined utilization of the TECNIS Eyhance and TECNIS Synergy IOLs (from now on referred to as ZFR00V/ICB00) remain unaddressed because of the lack of substantial evidence. 15,16,[20][21][22] Thus, we aimed to compare the clinical results associated with the use of ZFR00V in both eyes with those associated with the use of ZFR00V/ICB00.…”
mentioning
confidence: 99%